Health Effects and Life Stage Sensitivities in Zebrafish Exposed to an Estrogenic Wastewater Treatment Works Effluent - Cooper, Ruth; David, Arthur; Lange, Anke; Tyler, Charles R. (Frontiers in Endocrinology, 2021)
A wide range of health effects in fish have been reported for exposure to wastewater treatment work (WwTW) effluents including feminized responses in males. Most of these exposure studies, however, have assessed acute health effects and chronic exposure effects are less well established. Using an Estrogen Responsive Element-Green Fluorescent Protein (ERE-GFP)-Casper transgenic zebrafish, we investigated chronic health effects and life stage sensitivities for exposure to an estrogenic WwTW effluent and the synthetic estrogen 17α-ethinylestradiol (EE2). Exposure to the WwTW effluent (at full strength;100%) and to 10 ng/L (nominal) EE2 delayed testis maturation in male fish but accelerated ovary development in females. Exposure to 50% and 100% effluent, and to 10 ng/L EE2, also resulted in skewed sex ratios in favor of females. Differing patterns of green fluorescent protein (GFP) expression, in terms of target tissues and developmental life stages occurred in the ERE-GFP- zebrafish chronically exposed to 100% effluent and reflected the estrogenic content of the effluent. gfp and vitellogenin (vtg) mRNA induction were positively correlated with measured levels of steroidal estrogens in the effluent throughout the study. Our findings illustrate the importance of a fish’s developmental stage for estrogen exposure effects and demonstrate the utility of the ERE-GFP zebrafish for integrative health analysis for exposure to estrogenic chemical mixtures.